Semantic chemistry: an overview - Adams, Nico (Henry Stewart Talks, 2011)
Data is central, Work flow, Unstructured data and destructive publication formats, Object management, Semantic web, XML, MDL mol format, Chemical markup language, RDF, Linking open data cloud diagram, Sources of chemical data in RDF, What's a molecule?, Ontology definition, ebulliometry definition, Ontologic frameworks, A priori and a posteriori, Chemistry add-in for word, OSCAR1/OSCAR3, chemical entity extraction, Identification work-flow, Interannotator study, Applications, Chem2Bio2RDF, Web engine for non-obvious drug information, SADI, interoperable semantic web services